PP-033 Nystatin-lidocaine lozenges: innovation in the treatment of oral mucositis. (24th March 2015) - Cosme Silva, F; Marto, J; Salgado, A; Rodrigues, V; Ferreira, M; Almeida, AJ
Abstract : Background: Oral mucositis is often challenging to manage as the lesions can be very painful. It can compromise nutrition, oral hygiene and increase the risk of infection. It is important to develop oral formulations that enhance treatment compliance, improve the administration and ensure the effectiveness of the drug. Lozenges are described as an effective alternative to mouthwash, especially for their versatility, ease of administration and extended time in the oral cavity. Purpose: To describe the developmental process and stability studies performed of an innovative formulation of nystatin and lidocaine lozenges for the treatment of oral mucositis. Material and methods: An optimised lozenge formulation was developed. Different excipients such as gelatine, polyethylene glycol, sucrose, glycerine and gum arabic were tested. The aim was to obtain chemical and physical properties suitable for administration, storage and therapeutic compliance. Full pharmaceutical quality testing was carried out, specifically for this dosage form including disintegration and dissolution testing performed with artificial saliva. Appropriate stability-indicating analytical methodology (HPLC) was developed to quantify nystatin and lidocaine. The microbiological and stability tests are still ongoing. Results: A stable formulation of soft lozenges was obtained, presenting suitable palatability for oral administration. It can easily be compounded with standard hospital pharmacy equipment. The compounded product has suitable pharmaceutical characteristics, such as mass and content uniformity, disintegration time (15 min), dissolution rate and a pH value suitable for oral administration. Conclusion: Nystatin-lidocaine lozenges can be an effective alternative to mouthwashes for the treatment of oral mucositis due to their versatility, excellent palatability and easier administration. This formula's major advantage is the fact that patients can control for how long the drugs are retained in the oral cavity and consequently manage their pain treatment. The process of clinical application will validate efficacy and optimum dosing frequency. References: Marto J, Salgado A, Almeida AJ. Rev-Port-Farmacoterapia 2011;3(3):154–64 Strickley RG, Iwata Q, Wu S, et al . Pediatric drugs—a review of commercially available oral formulations. J Pharm Sci 2008;97:1731–74 No conflict of interest.